TOURIST OBJECT DEVELOPMENT ANALYSIS A COUNTRY ABOVE THE CLOUDS (LOLAI) IN INCREASING ORIGINAL REGIONAL INCOME OF TORAJA DISTRICT NORTH - Sri Devita Pasae; Andi Cudai Nur; Haedar Akib; Anisa Fitri (Jurnal Aktor, 2026)
This study aims to find out how the development of the State Tourist Attraction Above the Clouds (Lolai) in increasing Regional Original Revenue (PAD) of North Toraja Regency. This type of research uses qualitative with a descriptive method. Data collection uses literature study techniques, observations, interviews, and documentation. The data analysis technique uses SWOT analysis techniques. Based on the results of the SWOT analysis using the Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS) matrices, it shows that the development of the State Above the Cloud (Lempe Lolai) tourist attraction provides an increase in Regional Original Revenue (PAD) of North Toraja Regency. The results of IFAS and EFAS calculations show that a positive value means that the development conditions of the tourist attraction of the Land Above the Cloud (Lempe Lolai) are in good condition where the coordinates generated between IFAS and EFAS are in quadrant 1, namely X = 0.15 and Y = 1.1. This means that the tourist attraction is in a very favorable situation so that it has the power to take full advantage of the existing opportunities. Thus, the strategy that must be applied in the development of tourist attractions is an aggressive growth strategy (Growt Oriented Strategy).